2002
DOI: 10.1038/sj.onc.1205612
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of tumor susceptibility gene TSG101 in human papillary thyroid carcinomas

Abstract: Functional inactivation of tumor susceptibility gene tsg101 leads to cellular transformation and tumorigenesis in mice. While human TSG101 is located in a region where frequent loss of heterozygosity can be detected in a variety of cancers, no genomic deletion in TSG101 gene has been reported, casting a doubt on the role of TSG101 as a classical tumor suppressor. Some studies have revealed that TSG101 is a frequent target of splicing defects, which correlate with cellular stress and p53 status. Furthermore, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…However, excessive production of TSG101 also can promote abnormal cell growth (10), consistent with evidence for a cellular imperative to maintain TSG101 levels within a narrow range (19). Aberrant splicing of, partial deletions in, or overproduction of TSG101 protein have been reported to occur in human cancers (45)(46)(47)(48). Consistent with a crucial role of the intracellular level of TSG101 in determining its actions is evidence that cells that totally lack TSG101 cannot be propagated (8,9), whereas a lesser deficiency of TSG101 allows cell survival while still yielding prominent effects on endosomal trafficking and other biological processes (10,17,23,24).…”
Section: Discussionmentioning
confidence: 67%
“…However, excessive production of TSG101 also can promote abnormal cell growth (10), consistent with evidence for a cellular imperative to maintain TSG101 levels within a narrow range (19). Aberrant splicing of, partial deletions in, or overproduction of TSG101 protein have been reported to occur in human cancers (45)(46)(47)(48). Consistent with a crucial role of the intracellular level of TSG101 in determining its actions is evidence that cells that totally lack TSG101 cannot be propagated (8,9), whereas a lesser deficiency of TSG101 allows cell survival while still yielding prominent effects on endosomal trafficking and other biological processes (10,17,23,24).…”
Section: Discussionmentioning
confidence: 67%
“…16 However, a recent immunohistochemical study of TSG101 in human papillary thyroid carcinomas (PTCS) has shown that TSG101 expression levels were higher in PTCS than they were in normal cells. 17 We too have found TSG101 to be overexpressed in breast cancer cells, while the normal breast epithelial cells showed negative staining, though we did observe also that levels of this protein were decreased at the peripheral margin of the tumor. 1 Thus, whether TSG101 is consistently under-or overexpressed in a range of neoplastic tissues is not yet determined.…”
Section: Discussionmentioning
confidence: 78%
“…Tsg101 is upregulated in a subset of invasive human breast cancers There are only very few published studies that utilized methods other than reverse transcriptase-polymerase chain reaction (RT-PCR) to determine the expression of Tsg101 in primary human carcinomas (Lo et al, 2000;Liu et al, 2002;Zhu et al, 2003). All these reports demonstrated that the Tsg101 protein was expressed, albeit at heterogeneous levels, in normal and neoplastic tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Although the expression of Tsg101 appeared to be upregulated in selected human cancers (Lo et al, 2000;Liu et al, 2002;Zhu et al, 2003;and this report), the paradigm of Tsg101 as an oncogene has never been experimentally addressed using an appropriate in vivo model system. To test whether excess levels of Tsg101 are sufficient to trigger neoplastic transformation, we generated a transgenic mouse model that overexpresses wild-type Tsg101 in the developing mammary gland.…”
Section: Introductionmentioning
confidence: 99%